Morphometric analysis of the lens in human aniridia and mouse Small eye. (February 2021) - Voskresenskaya, Anna; Pozdeyeva, Nadezhda; Batkov, Yevgeniy; Vasilyeva, Tatyana; Marakhonov, Andrey; West, Richard A.; Caplan, Jeffrey L.; Cvekl, Ales; Wang, Yan; Duncan, Melinda K.
Abstract: Congenital aniridia is caused by heterozygous mutations in the PAX6 gene. In this disease, congenital iris and foveal hypoplasia is associated with juvenile onset cataract, glaucoma, and corneal keratopathy. In rodents, Pax6 mutations result in a congenital reduction in ocular size that is not typically described in human aniridia. Here, the ocular morphometry of aniridia patients is compared with the lens phenotype of Pax6 +/tm1/Pgr mice to reveal whether there are species differences in Pax6 regulation of lens development and homeostasis. Ultrasound biometry (UBM) revealed that eleven percent of aniridia patients exhibited mild microphthalmia while the anterior chamber depth of aniridic eyes was significantly reduced from 6 months of age onward. Although aniridic lens thickness was normal from birth, it was significantly decreased in aniridic lenses older than 30. Notably, 86% of aniridic lenses exhibited cataractous changes in this cohort. In addition, a significant proportion of aniridia patients develop lens subluxation as they age associated with reduced lens diameter as measured by anterior segment optical coherence tomography (AS-OCT). Analysis of young adult Pax6 +/tm1/Pgr mouse lenses by micro-computed tomography (microCT), bright field and dark field imaging revealed that they are reduced in size but did not exhibit overt cataracts at this age. Overall, this study reveals that congenital microphthalmia as assessed by axial length, or microphakia, as assessed by lens thickness, are not typical in human aniridia, although these are primary manifestations of Pax6 mutations in mice, suggesting that PAX6 regulates some aspects of lens development differently between these species. Highlights: 11% of aniridic eyes are modestly microphthalmic, although most were within the normal size range. Lens dislocation was common in the aniridia patients studied in this cohort. 86% of aniridia patients in this study exhibited cataract although the age of onset and cataract phenotype were variable. Mouse and human Pax6 mutations may have species-specific effects on the lens.